High-tech toys for your TV : secrets of TiVo, Xbox, ReplayTV, UltimateTV, and more - Kovsky, Steven D. (Que, 2002)
Take control of your digital living room! Make your TiVO, UltimateTV, XBox or GameCube do your bidding. We show you how to use these PCs in sheep's clothing to be king of your domain (or at least the area immediately surrounding your recliner). Like the plot from a circa 1950's sci-fi film, computerized look-alikes have surreptitiously replaced our VCRs, our video game consoles ... even our televisions and stereos. While the advantages that these digital entertainment devices (DEDs) offer over their analog predecessors are immense - so is the potential for sensory and information overload. Unlike the benign appliances we grew up with, these new digital wonders demand much more from us than the simple ability to turn them on and off. It's time to take control, put them through their paces, show them who's boss. The revolution in your living roomThe same forces that revolutionized the workplace during the past 25 years are now at work in our homes. The PCs in our dens were only the forerunners of this computer revolution. The real fireworks are taking place in the living room, where computers hidden inside our everyday appliances are poised to transform the way we live. Bottom line: Your days as a couch potato are numbered. TiVO and UltimateTV - changing the way you watch TV - forever! TiVO and UltimateTV are shaping up to be the white-hot category in home electronics for 2002. The merger of computers and traditional VCRs goes far beyond the superficial benefits of pausing and applying slow-motion and stop-action effects to live television. Learn the full range of these versatile machines. Choosing the right game console - You might not know it, we are amid a hardware slugfest between Nintendo, Sony and the dark horse, Microsoft. It's likely to be a battle as bloody as any depicted on the game consoles themselves. Compare the XBox, GameCube and Playstation2 side-by-side, and decide which console is right for you. Understanding the technical specs will help you make the right decision. Are you Feeling Lucky? Then, hacking your TiVO or UltimateTV box is just up your alley! You are truly the master of your digital domain. Not satisfied to let well enough alone, you're ready to venture into the unknown, in search of personal video recording nirvana. Kiss your warranty goodbye as you open up the box and truly push the envelope of digital entertainment. Not sure how to deal with the @#%^$@^ rat's nest of cables behind your entertainment center? Simmer d ...